Study on Micro - Nano Sized Al2O3 Particles on Mechanical, Wear and Fracture Behavior of Al7075 Metal Matrix Composites (Fracture and Structural Integrity, 2021)
Having Low density and being Light weight with better mechanical properties, aluminum is the most significant material and is universally used in highly critical applications like navy, aerospace and particularly automotive activities. This research work is aimed to investigate the effect of micro and nano boron Al2O3 (Alumina Oxide) to aluminium (Al) on the mechanical and wear properties of the Al composites. The micro - nano composites with 1, 2, 3 and 4 % of Al2O3 particulates in Al are fabricated using stircasting processes. It was found that an increase of Al2O3 both as micro and nano particulates content resulted in an improved hardness, enhanced tensile strength and high wear resistance. However, nano Al2O3 reinforced MMCs have better hardness, improved tensile strength and higher wear resistance as compared with micro sized Al2O3 reinforced MMCs. Grain refinement of composite and nano composite materials as compared with pure Al were observed from the microscopic images. Analysis of wornout surface and tensile fracture surface were studied by SEM analysis to examine the nature of wear and tensile fracture mode of composite samples.
Keywords: Al7075; Al2O3; Micro; Nano; Hardness; Tensile; Wear loss